If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -1x = 14 + -1 Combine like terms: 14 + -1 = 13 3 + -1x = 13 Solving 3 + -1x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 13 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 13 + -3 -1x = 13 + -3 Combine like terms: 13 + -3 = 10 -1x = 10 Divide each side by '-1'. x = -10 Simplifying x = -10
| 6(t-5)+6t=6(2t+2)-9 | | 3x=14-1 | | 3x+6=10x+14 | | 64=32-4(x-3) | | 12x+6=10x+14 | | 5(4x-1)=40 | | 5x-9x+14=5x+32 | | 5v-v+2= | | X+X[.2]=126 | | -(4y+3)-(-3y-6)=1 | | 7v-v= | | 0.90x+0.05(20-x)=0.10(95) | | 190p+10f=850 | | 35x-7y=-7x | | 124-2x=16x+24 | | 2x^4+x^2-x+6=0 | | 7[2-(4+2x)]-4x=-16+2(1-9x) | | -90-8x=8x+22 | | 2[k-(2k+12)+10]=2(k+2) | | 6x+11=-87-8x | | 5x+1y=0 | | 4x^3-12x+9=0 | | 6(v+2)-2v=2(2v+1)-3 | | 7y-2(y-2)=9y-(5y+12) | | x(x+8)=10 | | N=.03x-58.45 | | -3=x+5 | | x^2=8x-16 | | 6-3x=5x-10x+20-14 | | 6x^2-2x+5=0 | | 2x+9=49-3x | | 13x+2x=29-14x |